1997
DOI: 10.1111/j.1432-1033.1997.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ubiquitin Conjugation during Heat‐Shock Response Revealed by using a Monoclonal Antibody Specific to Multi‐Ubiquitin Chains

Abstract: Levels of intracellular multi-ubiquitinated proteins in heat-shocked HeLa cells were investigated using a monoclonal antibody specific to multi-ubiquitin chains. After heat-shock treatment at 42-44 "C for 30 min, the level of multi-ubiquitinated proteins increased within the first 2 h at 37°C and returned to the initial level within the following 2 h. The accumulation of multi-ubiquitin conjugates was elevated by increasing the temperature, while the opposite was the case for the level of ubiquitinated histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…The FK1 and FK2 antibodies specifically recognize ubiquitin-conjugated proteins, but not unconjugated ubiquitin (FK1 labels poly-ubiquitylated conjugates, FK2 labels mono-and poly-ubiquitylated proteins). 55,56 As shown in Figures 1b' and c', the immunoreactivity of FK1 and FK2 antibodies increases in prosβ2 mutant cells. We also find increased FK1 and FK2 labeling in Mov34 mutant cells (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 84%
“…The FK1 and FK2 antibodies specifically recognize ubiquitin-conjugated proteins, but not unconjugated ubiquitin (FK1 labels poly-ubiquitylated conjugates, FK2 labels mono-and poly-ubiquitylated proteins). 55,56 As shown in Figures 1b' and c', the immunoreactivity of FK1 and FK2 antibodies increases in prosβ2 mutant cells. We also find increased FK1 and FK2 labeling in Mov34 mutant cells (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 84%
“…Although accumulation of ubiquitin protein conjugates has been shown to occur with a number of stressors, a direct correlation between the availability of GSH in the cell and the accumulation of high molecular protein aggregates has not been established [34][35][36][37]. Bredfeldt et al observed that reduction in GSH levels could cause the accumulation of ubiquitinated proteins in UROtsa cells even though the actual level of GSH after GSH depletion by the Gcl inhibitor DL-buthionine-(R,S)-sulfoximine (BSO) in these cells was not documented [38].…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of ubiquitinated proteins were evaluated by Western blotting [14]. Soluble extracts of muscle homogenates were separated by 2-DE.…”
Section: Western Blottingmentioning
confidence: 99%